THE INFLUENCE OF COMPETENCE, INDEPENDENCE AND MOTIVATION ON APIP AUDIT QUALITY AT THE NORTH SUMATERA PROVINCIAL INSPECTORATE - Rihaney, Nine; Deliana, Deliana; Napitupulu, Ilham Hidayah (UPT Publikasi Ilmiah UNISBA, 2024)
Public demands for clean and KKN-free governance require the implementation of good supervisory functions by auditors over the implementation of government. Good government financial management must also be supported by good audit quality. Because if the quality of the audit is low, it is likely to provide leeway to make deviations use the budget. This study aims to (1) test the effect of auditor competence on audit quality, (2) test the effect of auditor independence on audit quality, (3) test the effect of auditor motivation on audit quality. The object of this research is at the North Sumatera Provincial Inspectorate Office. The sample in this study was 37 (Thirty-Seven) Auditors and Supervisors at the North Sumatera Provincial Inspectorate Office. Data collection is implemented by means of questionnaire method. The research method used is Partial Least Square (PLS) analysis using the Smart PLS 4.0 application. The results of this study show that (1) auditor competence has a positive effect on audit quality, (2) auditor independence has a positive effect on audit quality (3) auditor motivation has a positive effect on audit quality. Keywords : Competence, Motivation, Independence, Audit Quality.